The Effect of the Rebozo and Effleurage Techniques on Reducing Contraction Pain During Labor at TPMB Lina Maryati in 2022 - Lina Maryati; Nursitiyaroh Nursitiyaroh (CV. Inara, 2023)
Pain that lasts from the first stage to the third stage of labor is referred to as labor pain. Apart from being a subjective experience, labor pain is also the result of physical sensations caused by uterine contractions, cervical dilatation and effacement, and fetal descent. Purpose of Writing: to determine the Effectiveness of the Rebozo and Effleurage Techniques in Reducing Contraction Pain During Labor at TPMB Lina Maryati in 2022. Research Methods: In this study it was experimental (quasi-experimental) with a control group design and an experimental group with a quantitative approach. Sampling in this study was a total sampling of 15 people. The sample technique used was accidental sampling. Research results: between using the rebozo and effleurage techniques before and after the mean rank was 8.00 and the sum rank was 120.00. A value of 15 means that this result indicates a decrease (reduction) from the value before and after meaning that all respondents who experienced contraction pain during labor had a reduction in contraction pain using rebozo and effleurage so that it was concluded that there was a significant difference in the pain scale of contractions before and after the rebozo technique was carried out and effleurage, thus it can be concluded that the rebozo and effleurage techniques are effective in reducing contraction pain or in other words, there is effectiveness of the rebozo and effleurage techniques in reducing contraction pain during labor. Conclusions and Suggestions: can be a guideline for health workers, especially midwives in applying this technique to mothers in labor in an effort to reduce or eliminate pain experienced by mothers during contractions.